Lynx lynx - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2009)
23. Eurasian Lynx Lynx lynx French: Lynx d'Europe / German: Eurasischer Luchs / Spanish: Lince boreal Taxonomy. Felis lynx Linnaeus, 1758, Wennersborg, S Sweden. Seven subspecies recognized. Subspecies and Distribution. L. l. lynx Linnaeus, 1758 — N and W Europe E to the Yenisei River in Russia. L. l. carpathicus Kratochvil & Stollman, 1963 — Carpathian Mts S to Bulgaria and Greece. L. l. dinniki Satunin, 1915 — Caucasus Mts S to Turkey and N Iran. L. l. isabellinus Blyth, 1847 — Pamir and Kunlun Mts, Kashmir, C & W China. L. l. kozlovi Fetisov, 1950 — C Siberia, from the R Yenisei to Lake Baikal. L. l. neglectus Stroganov, 1962 — Russian Far East, Korea, and NE China (Manchuria). L. l. wrangeli Ognev, 1928 — E Siberia, S to the Stanovoy Mts. Descriptive notes. Largest of the four lynx species. Head-body 80-110 cm, tail 16-23 cm; weight 15-29 kg (unconfirmed over 30 kg) for adults; males 25% heavier than females. The speciesis largest in the eastern portion ofits range. Characteristic of the genus,it has a short, black-tipped tail, black ear tufts up to 6 cm long, and relatively long legs. The hindlegs are longer than the front legs. The round face is framed by pronounced sideburns. Reduced number of molars and 28 teeth in total: 13/3, C 1/1, P 2/2 and M1/1. About 30% of the animals have a second reduced molar in the lower jaw. There are four different coat patterns on a ground color that varies (grayish, rusty, yellowish, or reddish): large black spots, small black spots, no spots, and spots in form of brownish rosettes. The proportion of these types varies greatly between populations. Habitat. Deciduous, mixed, and coniferous forests in Europe and Siberia; fairly open and sparsely wooded regions, including semi-deserts in Central Asia. Thick scrub woodland and barren, rocky areas throughout the northern slopes of the Himalayas. In northern latitudes, also roam in the tundra. Food and Feeding. In contrast to the three other lynx species, the Eurasian Lynx is not a hunter of lagomorphs, but of smaller ...